COMPREHENSIVE REVIEW ON ADVANCES IN PAIN MANAGEMENT TECHNIQUES IN EMERGENCY MEDICINE. - 1Hadi Saleh Hadi Alduways, 2Ibrahim Musallam Hassan Alduways, 3Ismail Miqradh Abdallah Al Atmi, 4Abdallah Mana Hamad Qutayshan, 5Hadi Hussain Bin Hadi Al Duways, 6Hussain Mohammed Hamad AL sulaiman, 7Hadi Hamad Yousef Al Sulaiman, 8Mana Mohammed Mana Alth (Chelonian Research Foundation, 2022)
Pain management in crisis pharmaceuticals is imperative for progressing patient results, and progressed advances show up to be made in pharmacological interventions. This survey gives an in-depth look at the most recent developments in pain management procedures in emergency medicine, centred on pharmacological administrations, regional anesthesia frameworks, non-chemical strategies, and innovation integration. By synthesizing the existing writing and checking on the strategy utilized in related study, this audit presents key discoveries alongside charts and tables. This survey highlights the significance of a pharmacological approach to pain management in crisis settings, giving knowledge into the effects of these progresses on healthcare through a basic investigation. At long last, proposals are advertised to make strides in pain management procedures and advance the patient care and curiosity in emergency medicine. Keywords: Pain management, emergency medicine, pharmacological interventions, regional anesthesia, non-pharmacological approaches, technology integration.